Adaptation Test Variety of Cabbage Plant on the Reduction of Light Intensity - Effendi, Mokhtar; Sugito, Yogi; Nugroho, Agung (RADIKULA: Jurnal Ilmu Pertanian, 2023)
Cabbage (Brassica oleracea) is a vegetable commodity that has high economic value so it is widely cultivated by farmers in various countries. Data from the Central Statistics Agency (BPS) and the Directorate General of Horticulture show that in 2013 the cabbage harvest area in Indonesia was 65,248 ha, with production of 1,480,625 tons and productivity of 22.69 tons / ha (Central Statistics Agency and Directorate General of Horticulture , 2013). Opportunities for cabbage business development are increasingly widespread. The general public began increasingly fond of cabbage because in addition to good taste and as a vegetable food ingredient also because it contains quite high nutrition. Climate elements such as air temperature, solar radiation, and humidity support and play an important role in plant production. This is because plants need climate elements, especially the intensity of solar radiation. Each plant requires a certain range of solar radiation intensity for its growth, there are plants that require high light intensity and some are low. Processes in plants that can be affected by light intensity are photosynthesis, transpiration, respiration, nitrate reduction, protein synthesis, hormone production, translocation, aging, root growth and nitrate absorption (Struik and Deinum, 1982). In the development of cabbage cultivation one of the problems that has the potential to occur in the development of these plants is the low intensity of sunlight received by plants due to the shade of various objects or other plants so that plants do not get enough sunlight for their growth. Therefore, studies are needed to study how the adaptation of cabbage plants to a decrease in light intensity. According to Wolff and Coltman (1990) a reduction in the intensity of sunlight up to 30% to 47% can still be tolerated by cabbage plants. However, these conditions are apparently still within the limits of plant tolerance so that plant growth is not disrupted.